Disciplinary differences in the experience of online education among teachers and students in Chinese universities during COVID-19 - Shuo Yu; Ying Liu; Bingqing Yang; Zhiwei Chen (Frontiers in Psychology, 2022)
Online education has advantages during COVID-19, but it also has problems related to hardware support and user experience. Focusing on teaching quality by discipline is an effective way to improve teaching quality in universities. To investigate the online education experience from the perspective of different academic disciplines, we evaluated 251,929 student questionnaires and 13,695 teacher questionnaires from 334 universities in China. The main finding was a difference in teaching preparation, experience, feedback, and improvement processes by disciplines. Teachers and students had obvious disciplinary differences in preparation, school support, and teaching constraints. However, disciplinary differences were minor for pedagogical issues such as participation, assignments, and grading, as well as for evaluation of platform technical support and views on the continuation of online learning. The research results analyzed the teaching psychology of teachers and students in different disciplines during the pandemic. Therefore, it explained the impact and role of discipline differences on students’ learning psychology during COVID-19. This research will benefit educators, researchers, and policy makers to help them with the improvement of online education.